Environmental & architectural phenomenology. Vol. 7, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 1996)
Vol. 7, No. 1, Winter 1996 (includes “items of interest,” "citations received,” book reviews of Watsuji Tetsuro's Climate and Culture & Michael Greenberg's The Poetics of Cities, and essays by Eric Angell & Ron Walkey).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals